2016
DOI: 10.1002/eji.201646395
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic neural signaling via the β2‐adrenergic receptor suppresses T‐cell receptor‐mediated human and mouse CD8+ T‐cell effector function

Abstract: Post-ganglionic sympathetic neurons innervate secondary lymphoid organs and secrete norepinephrine (NE) as the primary neurotransmitter. NE binds and signals through 5 distinct members of the adrenergic receptor family. In this study, we show elevated expression of the β2-adrenergic receptor (ADRB2) on primary human CD8+ effector memory T cells. Treatment of both human and murine CD8+ T cells with NE decreased IFN-γ and TNF-α secretion and suppressed their cytolytic capacity in response to T-cell receptor (TCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 48 publications
5
77
2
Order By: Relevance
“…NE signaling through β 2 -ARs on lymphocytes has recently been shown to suppress immune cell function in non-oncological settings (17,23,24), therefore we asked whether this signaling pathway mediates immune suppression in mice housed at 22°C. We repeated the experiments shown above (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…NE signaling through β 2 -ARs on lymphocytes has recently been shown to suppress immune cell function in non-oncological settings (17,23,24), therefore we asked whether this signaling pathway mediates immune suppression in mice housed at 22°C. We repeated the experiments shown above (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As they point out, NE signaling through β-ARs on CD4 + lymphocytes induces production of the T H 2 cytokines IL-6 and IL-10 suppressing production of the T H 1 cytokines IL-12, TNF-α and INF-γ thereby reducing the generation of cytotoxic CD8 + T cells. Recently, Estrada et al, investigated adrenergic signaling specifically in CD8 + T cells and found that β 2 -AR activation decreased IFN-γ, TNF-α, and IL-2 production and suppressed the ability of CD8 + T cells to kill virally infected cells (24). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations